The Effect of Combined Stimulation of Baby Massage and Lavender Essential Oil on Gross and Fine Motor Skills in Infants Aged 3–12 - Rani Safitri; Fadlila Ammari; Rosyidah Alfitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Gross motor and fine motor development are critical aspects of early childhood growth, yet a significant proportion of infants and toddlers continue to experience delays in these areas. According to the World Health Organization (WHO) in 2016, approximately 20–40% of infants aged 0–2 years face delays in developmental processes, with 5–25% experiencing gross and fine motor disorders. Delays in gross motor skills can reduce adaptability and creativity during the adaptation period, while delays in fine motor skills may hinder a child’s learning process. Beyond adequate nutrition provided by the mother, stimulation is an essential strategy to optimize growth and development. One promising approach is the combination of baby massage and lavender essential oil, which may offer both physical stimulation and relaxation benefits that support motor skill advancement. This study aims to determine the effect of combined baby massage stimulation and lavender essential oil application on the improvement of gross and fine motor skills in infants aged 3–12 months. A pre-experimental quantitative design with one-group pretest–posttest was applied to a sample of 40 infants. Data analysis employed the Wilcoxon signed-rank test to assess changes in motor development scores before and after the intervention. Results indicated a probability value (p-value) of 0.02 (<0.05), suggesting a statistically significant improvement in both gross and fine motor skills following the intervention. These findings highlight the potential of integrating tactile and aromatherapy-based stimulation into infant care routines to enhance motor development. Further research with larger and more diverse samples is recommended to validate these results and explore the underlying mechanisms of action.